The Effect of Working Discipline and Training on Employee Performance (at PT. Transkom Indonesia in Tangerang) - Maduningtias, Lucia (Universitas Negeri Makassar, 2018)
One of the organizational resources that has an important role in achieving its goals is human resources. This study aims to determine the effect of work discipline and training on employee performance at PT. Transkom Indonesia in Tangerang. The method used is a descriptive method with an associative approach, while to get the data done by distributing questionnaires to 90 respondents. The results of work discipline research have a positive and significant effect on employee performance by 35.0%. Hypothesis testing obtained t count> t table (6.887> 1.987). Training has a positive and significant effect on employee performance by 45.5%. Hypothesis testing obtained t count> t table (8.578> 1.987). Work discipline and training have a positive and significant effect on employee performance with a regression equation Y = 10.908 + 0.262X1 + 0.479X2. These results indicate the coefficient of work discipline variables of 0.262 and training of 0.479, all variables are positive meaning that the better discipline and training, the better the performance of employees. The contribution of the influence of work discipline and training was 51.6% while the remaining 48.4% was influenced by other factors. Hypothesis testing obtained F count> F table (46,364> 3,100), thus H0 is rejected and H3 is accepted meaning that there is a positive and significant influence between work discipline and simultaneous training on the performance of Transkom Indonesia employees in Tangerang.